PENGARUH KEADILAN PROSEDURAL, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Ni Putu Ayu Sintya Saraswati (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2017)
This study aims to determine the effect of prosedural, organizational culture and job satisfaction on OCB in PT. Ciomas Adisatwa is located at JL Raya Kaba Kaba, Dauh Yeh, Kediri, Tabanan. Population in research is all employees of PT. Ciomas Adisatwa. The sample in this research is permanent employee which amount to 34 people.Data analysis technique used multiple linear regression analysis.The results show that prosedural justice has a positive and significant effect on OCB,organizational culture has a positive and significant impact on OCB and job satisfaction has a positive and significant effect on OCB.